An evaluation of cation exchange capacity methods for acid tropical soils - Ishak, Cek Fauziah; I., Jamilah; Syed Rastan, Syed Omar (Universiti Putra Malaysia Press, 1997)
The cation exchange capacity (GEC) of soil is an important criteria for assessing soil fertility beside its use in soil classification. Seven methods, namely, (1) BaCl2 - triethanolamine of BaCl2 - TEA (PH 8.2), (2) NH40Ac (PH 7.0) - leaching, (3) NH40Ac (PH 7.0) - shaking, (4) compulsive exchange method of Gillman (1979) (GECcd, (5) modified compulsive exchange method of Gillman (1986) (CEC3, (6) Summation of Ca from method 5 with 1 M NH4 NO3 exchangeable Al (CECtotal and (7) summation of NH40Ac (PH 7.0) exchangeable bases with 1 M KCl exchangeable Al (CECsum) were used to determine and compare the CEC values of five acid tropical soils. All methods gave different CEC values which followed the order BaCl2 - TEA> NH40Ac shaking = NH40Ac leaching> CECsum = CECto tal > CECCE = CECB• Methods with pH conditions close to field situations gave much lower CEC values than the buffered methods. The buffered methods generate charge on the variable-charge colloids, thus resulting in inflated CEC values, while the unbuffered methods do not. There is a high correlation between BaCl2 - TEA and NH40Ac (PH 7. 0) leaching method; CECCE and CECsum; and, CECB and CECtotal Amongst the methods evaluated, the NH40Ac (PH 7.0) leaching is recommended in routine soil analyses for classification purposes while CECsum is recommended for agronomic evaluation.